Transcutaneous tibial nerve stimulation for the treatment of faecal incontinence: results of a prospective study - Stundienė, Ieva; Žeromskas, Paulius; Valantinas, Jonas (Acta medica Lituanica, 2014)
Background. Transcutaneous tibial nerve stimulation is a simple, non-invasive treatment, which can be used to treat faecal incontinence. Optimal treatment regimen is not known and various stimulation regimens are used in different centers. The aim of this prospective study was to evaluate the efficacy of twice weekly transcutaneous tibial nerve stimulation for faecal incontinence patients, who have failed to respond to maximal conservative treatment. Material and methods. Twenty patients with faecal incontinence resistant to maximal conservative therapy were treated with transcutaneous posterior tibial nerve stimulation twice a week for six weeks. The number of the bowel movements per two weeks and the Cleveland Clinic Florida Feacal Incontinence Score were assessed before and after the treatment. The quality of life was estimated using the Faecal Incontinence Quality of Life questionnaire and the Gastrointestinal Quality of Life Index. Results. Effect was seen in 55% of patients. Two-week faecal incontinence episodes decreased from median 4 (2–84) to 2 (0–56) (p = 0.002). The mean Cleveland Clinic Florida Faecal Incontinence score improved from 10.9 ± 4.34 to 7.8 ± 3.96 (p = 0.002). The quality of life improved significantly after the treatment. The therapy was well tolerated and no participant experienced any adverse event. Conclusions. Transcutaneous tibial nerve stimulation twice a week for 6 weeks may be efficacious in patients with faecal incontinence, who have failed to respond to maximal conservative treatments.